Factores predictores del consumo de alcohol en adolescentes: datos de un estudio prospectivo de un año de seguimiento (2019)
Alcohol use/abuse is a health problem in adolescents. The last Survey on use of drugs in Secondary Schoolers carried out in Spain (ESTUDES 2014-2015), reveals that 76.8% of adolescents aged 14 to 18 years consumed alcohol in the previous year and 68.2%